Changes in oxidative stress markers during electro-ejaculation procedure in merino rams - FIDAN, A. F.; YENI, D.; AVDATEK, F.; ÖZÇINAR, Ü.; HAZMAN, Ö. (Journal of the Hellenic Veterinary Medical Society, 2018)
Electro-ejaculation is a technique used to collect semen from rams. The aim of the study was to evaluate the stress response and the oxidant/antioxidant levels during electro-ejaculation (EE) procedure in merino rams. To assess the effect of this technique, six 3-4 years old merino rams were subjected to semen collection by EE. The technique was applied one time in previously untreated animals. The studied parameters [Heart and respiratory rate, rectal temperature, white blood cell count (WBC), red blood cell count (RBC), hemoglobin (Hb) levels, hematocrit (Hct) value, blood malondialdehyde (MDA) and glutathione (GSH) concentrations, plasma cortisol, nitric oxide (NO), glucose, cholesterol and triglyceride concentrations as well as plasma total antioxidant status (TAS) and total oxidant status (TOS)] were measured before and immediately after electrical stimulation. Heart and respiratory rate, WBC, MDA, glucose, cholesterol and triglyceride concentrations as well as plasma TOS and cortisol concentrations were dramatically increased after EE procedure, whereas rectal temperature, TAS and GSH concentrations were significantly decreased. These results demonstrate that MDA, GSH, TAS and TOS were the most powerful markers for evaluating the oxidant/antioxidant status in merino rams. Furthermore, EE procedure was a stressful situation leading to an oxidative stress, which can be amplified by increased glucocorticoid secretion.